Diet of the Dusky finless skate Gurgesiella furvescens (Chondrichthyes: Rajidae) from the continental shelf and slope of the north-central area of Chile (Revista de Biología Marina y Oceanografía, 2022)
The dusky finless skate Gurgesiella furvescens appears sporadically as part of the bycatch in the trawl fishery targeting demersal crustaceans on the continental shelf and upper slope of the north-central area of Chile (26ºS-33ºS). Demersal crustaceans could be forage for deep-water predators such as G. furvescens, and sizes and shapes of prey eaten could be restricted by mouth size. The diet composition of G. furvescens was determined based on specimens collected from the bycatch of trawls targeting demersal crustaceans in 2013. Analysis of the stomach contents revealed that the diet was mainly nylon shrimp Heterocarpus reedi (32.8% by weight), deep-water shrimp Haliporoides diomedeae (7.2% by weight), and indeterminate crustaceans (9.0% by weight). The diet composition was similar between sexes, body length, or depth strata. Prey size was a linear function of Gurgesiella furvescens mouth width, and prey mass positively related with G. furvescens individual mass. Although squat-lobsters Pleuroncodes monodon and Cervimunida johni were abundant in the study area, the presence of nylon shrimp and deep-water shrimp in the diet of G. furvescens may be due to the preference or selection of this type of prey in deep waters.